Pengembangan Game Math Story Problems Menggunakan RPG Maker MZ untuk Anak 4-7 Tahun - Nuraminudin, M.; Astuti, Ika Asti; Susanto, Sebastian Arby (Edu Komputika Journal, 2022)
This study aims to produce and test the feasibility of an RPG (Role Playing Game) Math Story Problem created using the RPG Maker MZ software. The research method used is the Research and Development method using research stages (1) needs analysis, (2) design, (3) implementation, (4) validation, (5) revision and (6) product testing. The requirements analysis stage is used to analyze competency standards, hardware and software specifications. The design stage includes storyline design, display design, flowchart and character creation in the game. The implementation stage is the stage of realizing the design into an actual product. The validation stage is carried out to assess the feasibility of the game that has been designed and created which is then determined by the experts to get the criticism and suggestions needed for improvement so that the game becomes even better. The trial phase is carried out by direct application in children's learning. This test was conducted on respondents aged 4-7 years using a questionnaire. The data obtained were processed by descriptive analysis to determine the level of feasibility of the game. The results of data analysis showed that the feasibility level according to material experts was 96% which was included in the very feasible category and children as users was 83.75% which could be categorized as very feasible.